A Career Counseling Model as a Therapeutic Approach for Students with Intellectual Disabilities - Noorsofiana Affandi; Asmah HJ Husaini (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Career counseling is crucial for students with intellectual disabilities, enabling them to develop the skills and knowledge necessary for future employment. These students require personalized career guidance that addresses their unique abilities and challenges. Objective: This study aimed to investigate the planning and implementation of career guidance for students with special needs at the senior high school level. Method: A qualitative phenomenological approach was used to examine students' experiences and perceptions of the career guidance process. The research, conducted in 2025 at government secondary schools within the Brunei-Muara district, involved 14 students. Data were collected through observations, in-depth interviews, and documentation, and analyzed using Miles & Huberman's interactive model. Result: Career guidance was highly individualized, focusing on each student's abilities and needs. Demonstration methods were commonly employed, with clear and instructive steps to ensure comprehension and skill acquisition. Conclusion: Career guidance at government secondary schools within the Brunei-Muara district was effectively implemented using individualized, instructive approaches with demonstration techniques to meet students' unique learning needs. Contribution: This study makes a significant contribution to special education and career counseling by highlighting the need for adaptive and individualized career guidance models for students with intellectual disabilities. It offers valuable insights for educators, counselors, and policymakers on creating inclusive career programs within special education institutions.